2022
DOI: 10.1158/1078-0432.ccr-22-1006
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Germline Cancer Susceptibility Gene Variants in Individuals with Non–Muscle-Invasive Bladder Cancer

Abstract: Purpose: Identification of inherited germline variants can guide personalized cancer screening, prevention, and treatment. Pathogenic and likely pathogenic (P/LP) germline variants in cancer predisposition genes are frequent among patients with locally advanced or metastatic urothelial carcinoma, but their prevalence and significance in patients with non-muscle invasive bladder cancer (NMIBC), the most common form of urothelial carcinoma, is understudied. Experimental Design: Germline analysis was conducted on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…(13). In 2014, there were about 78100 new cases of bladder cancer in China, with a standardized incidence rate of 3.61/100000, about 32100 deaths, and a standardized mortality rate of 1.30/100000 [ 23 ]. Despite China has lower bladder cancer rates and fatality rates than the rest of the globe, it still shows an increasing trend in the past decade, and has become one of the important disease burdens in China [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13). In 2014, there were about 78100 new cases of bladder cancer in China, with a standardized incidence rate of 3.61/100000, about 32100 deaths, and a standardized mortality rate of 1.30/100000 [ 23 ]. Despite China has lower bladder cancer rates and fatality rates than the rest of the globe, it still shows an increasing trend in the past decade, and has become one of the important disease burdens in China [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…. In 2014, there were about 78100 new cases of bladder cancer in China, with a standardized incidence rate of 3.61/ 100000, about 32100 deaths, and a standardized mortality rate of 1.30/100000[23]. Despite China has lower bladder…”
mentioning
confidence: 99%
“…Constitutive expression of PD-L1 on cancer cells could result from mutations in DNA damage repair genes or could be induced via the phenomenon of adaptive immune resistance during disease progression [39]. While the mutational profiles of tumors used in our study were not available, previous studies have reported an enrichment of DNA damage repair gene mutations in high-grade NMIBC tumors [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that the study of iUC in canine populations may fill in gaps in studies of bladder cancer in humans. The numerous cohorts amassed for studies of human bladder cancer risk feature, on average, > 80% males and 80–85% non-muscle invasive disease 68 71 , even though muscle invasive bladder cancer carries a much higher risk of early mortality 72 . Women are underrepresented in these studies because they are less likely to get bladder cancer than men, however they more often get invasive disease and their relative survival expectancy is reduced by five percentage points or more across all stages of the disease ( https://seer.cancer.gov/ ).…”
Section: Discussionmentioning
confidence: 99%